Revisitando e ressignificando produções acadêmica sobre pedagogia hospitalar no âmbito da Universidade Federal do Pará - PEREIRA, Renata Kelly Ribeiro (2020)
The present research is the result of bibliographical revisions focusing on the area of Pedagogy Hospital, in which it seeks to understand, analyze and study the Course Completion Works belonging to the Faculty of Education at the Universidade Federal do Pará. The research was guided by the works of conclusion of course that worked on the subject of Pedagogy in hospital environments, with the purpose of resignifying the studies on the subject, revisiting and analyzing the Monographs and Works of Conclusion of Course presented and defended in the “Instituto de Ciências da Educação” - ICED, that is, doing a search and revision of the proposed theme regarding a perspective of discussion of the new visions of teaching about the hospital education. Thus investigating the importance of teaching outside the educational environments and the pedagogical practices developed by the professionals of the area, thus enabling a descriptive and investigative research on Education in non-school environments and their possibilities of teaching, considering the historical construction of PH through the legislations, the different nomenclatures that surround the theme, besides revisiting the works of TCC of the course and thus resignifying the same ones to better involve the research on Hospital Pedagogy